Making sense of the "raw meat": A social semiotic interpretation of user translation on the danmu interface. (December 2021) - Yang, Yuhong
Abstract: The danmu interface is a unique feature on Japanese and Chinese video-sharing websites which allows "live" comments to be directly overlaid onto the video. This paper focuses on one particular semiotic and social practice materialised on the danmu interface, collaborative user translation, where users use their danmu entries to post translations onto the video frame in their engagement with the "raw meat", untranslated foreign language videos. Adopting Theo van Leeuwen's social semiotic approach to visual communication and his conceptualisation of "semiotic regimes", this study explores how such a translation practice materialises on the danmu interface through an investigation of the use of semiotic resources in relation to relevant semiotic regimes that derive from the semiotic technology of danmu, professional practices of audiovisual translation and relevant regulatory discourses. Multimodal discourse analysis is conducted on a dataset consisting of an untranslated English documentary video posted on Bilibli, the most popular danmu video website in China, and 1973 entries of danmu comments archived on the interface. This paper contributes to the development of social semiotics-oriented multimodal discourse analysis through a focus on the semiotic and social practice of user translation on danmu, adding more depth to existing studies on such a practice, and broadens the scope of non-professional translation studies.